EXCRANIZATION OF THE NOVEL "NANTI KITA CERITA TENTANG HARI INI" AS A MODERN POPULAR COLLABORATION - Desyarini Puspita Dewi; Fifi Al Afiyah (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Indonesian films are increasingly in demand by the Indonesian people, one of which is ecranized films. Literary work that is translated can change its elements to suit a new vehicle, so that there will be differences between the literary work such as novels and other media such as films, even though the source is the same. These similarities and differences affect the emergence of ecranization in the form of shrinking, adding and varying changes in the plot, characterizations and setting between the novel and the film. The type of research used is a content study with a qualitative approach and descriptive method. The data collection technique used is the use of documents with reading, listening and note-taking techniques. The results of the analysis in this study found 5 similarities and 1 difference between the novel and the film. In addition, there was a contraction in the plot, characterizations, setting of place and time. The additions are in the plot, characterizations, and place settings. While the changes vary in the plot and time setting. The popularity of an ecranization can provide mutually beneficial results from the collaboration between the novel and the film adaptation.